KARAKTERISASI RESERVOAR BATUPASIR PADA FORMASI PLOVER DI LAPANGAN âMATAâ SAHUL PLATFORM CEKUNGAN BONAPARTE DENGAN MENGGUNAKAN INVERSI SEISMIK IMPEDANSI AKUSTIK BERBASIS MODEL - , ANACLETO PEREIRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hydrocarbon reservoir characteristics are complex and heterogeneous nature of the type of formation. The Reservoir problems will decrease the success ratio in oil and gas drilling. This study restricted in effort to know the characterisation and maping the sandstone reservoir zones at the Plover Formation in \"Mata\" Sahul Platrom Bonaparte Basin using based model inversion method. The data used in this study are well log data, seismic data 2D post-stack, check- shoot data and geological data. Based model inversion method was applied to the inversion process of seismic data. The result of this inversion process was model of acoustic impedance. Determining the value of the acoustic impedance and the process map slice to be analyzed the distribution of sandstone reservoir. An Integrated interpretation of the time structure map, acoustic impedance valueâs, gamma ray valueâs and impedance aqoustic map were used to determine the reservoir sandstones zone and their distribution. The interpretation results indicated that the accumulation of sandstones reservoir is located in the high structure area and spread in the northeast - southwest. The target of sandstone reservoir zone has an acoustic impedance valueâd 5400-9250 m/s.g/cc and gamma ray valueâd 10-74 API.